2021
DOI: 10.1051/epjconf/202124903033
|View full text |Cite
|
Sign up to set email alerts
|

Drag of a cylindrical object in a two-dimensional granular environment

Abstract: The drag of a cylindrical object in a two-dimensional granular environment is numerically studied. It is found that the drag law is fitted by the sum of the yield force and the dynamic force, the latter of which is reproduced by a simple collision model. The angular dependence of the radial stress on the surface of the object is given by the Gaussian below the yield force. The probability of the velocity drops of the object is investigated above the yield force, where this probability is independent of the pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is noted that the increasing rate of V depends on the distance ∆. Here, in the case of a single intruder, we previously reported that the relationship between the drag force F drag and the steady speed V is given by [13]…”
Section: Drag Lawmentioning
confidence: 91%
See 2 more Smart Citations
“…It is noted that the increasing rate of V depends on the distance ∆. Here, in the case of a single intruder, we previously reported that the relationship between the drag force F drag and the steady speed V is given by [13]…”
Section: Drag Lawmentioning
confidence: 91%
“…Using the same procedure in Ref. [13], the stress field can be constructed in terms of the Airy stress function χ as…”
Section: Stress Fields Around Intrudersmentioning
confidence: 99%
See 1 more Smart Citation
“…The drag experienced by spherical and cylindrical intruders has been observed to scale linearly with the overburden weight of the sediments and crosssectional area when the intruder size is much greater than the sediment size [14][15][16]. The dynamic force resulting from granular collisions becomes important with speed and has been calculated in dry granular materials [17]. Presence of interstitial liquid influences the drag in granular beds [18][19][20], but remains relatively less studied compared to the dry granular case [21,22].…”
Section: Introductionmentioning
confidence: 99%